2015
DOI: 10.3390/h4040958
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Hermeneutic Analysis of Presence in Nursing Practice

Abstract: Nursing presence, although it involves action at times, is a humanitarian quality of relating to a patient that is known to have powerful and positive implications for both nurse and patient. However, this phenomenon has not been well understood. Three theories, drawn from the work of Paul Ricoeur and Hans-Georg Gadamer, served as the boundaries for both data collection and analysis. The theories were narrative identity, play and solicitude. This study follows a critical hermeneutic approach to field research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
14
0
3
Order By: Relevance
“…[ 32 ] Bright believes that the presence of a nurse, even a physical presence minus therapeutic action at times when treatment and palliative care fall short of the patient's needs, can change the quality of care from the patient's perspective. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] Bright believes that the presence of a nurse, even a physical presence minus therapeutic action at times when treatment and palliative care fall short of the patient's needs, can change the quality of care from the patient's perspective. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da importância dispensada aos diários de Florence Nightingale, o conceito de Presença na prática de Enfermagem surge em 1962, juntamente com a filosofia e a fenomenologia existenciais, através dos manuscritos da Irmã Madeleine Clémence Vaillotque tentou aplicar a filosofia de Gabriel Marcel e Martin Heidegger à Enfermagem, defendendo que a presença existe quando o enfermeiro prima pela qualidade do compromisso (3,5,8,11) . Ideia semelhante é retomada por Hildegard Peplau (1952), a primeira teórica a considerar a relação terapêutica como o núcleo da enfermagem, enfatizando o uso terapêutico do self, destacando a autorreflexão e a autoconsciência como habilidades necessárias para todos os enfermeiros (20) .…”
Section: Evolução Do Conceito Presençaunclassified
“…A Presença é um conceito complexo, matizado central para vários modelos e teorias de enfermagem (1) . Qualidade humanista do relacionamento estabelecido com um utente, que pode ser denominado de phronesis (2) , excelência do intelecto prático ou sabedoria moral prática que beneficia o utente e o enfermeiro (1,3,4,5,6,7,8) .…”
Section: Introductionunclassified
“…And by this may enhance to achieve calmness through some strategies to make them behaving successfully. While; Bright[42] has clarified the role of ethical orientation, creativity and connection with the human experience through exploration of self and other. However, Koskinen & Nystrom[43] had central foundations in the application of research which are ethics, creation of a hermeneutical room, dialogue and common understanding and appropriation and action.…”
mentioning
confidence: 99%
“…The study of lived experiences of elderly patients with Coronary Artery Disease of Karimooi et al[41] shown one main theme: living with ups and downs, with sub-themes: losing calmness, trying to achieve calmness through spirituality, losing health, trying to promote health through modification of lifestyle, perceiving family support, living in fear, and living with a damaged heart. However, Bright[42] had explored and examined the phenomenon of nursing presence through the hermeneutic lenses. Theoretical categories include: narrative identity, play and solicitude, whereas, Koskinen and Nystrom [43] contributed to the development of the hermeneutical application research design in its epistemological, ontological and ethical perspective, by articulating and clarifying the central foundations in the application.…”
mentioning
confidence: 99%